Development of a Multidimensional Measure to Examine Fear of Dementia. (September 2019) - Page, Kyle S.; Hayslip, Bert; Wadsworth, Dee; Allen, Philip A.
Persons with and without a family history of dementia report concerns for developing this syndrome; yet, less is known about the specific aspects of dementia that are feared. The Fear of Dementia (FOD) scale was created to assess these concerns. This study examined the psychometric properties of the FOD scale using a sample of middle-aged and older adults ( N  = 734). We then explored the factor structure of the scale 2 years later using a smaller sample from the first study ( N  = 226). Three factors emerged, highlighting several main areas of concern: Burden and Loss, Quality of Life, and Perceived Social and Cognitive Loss. Preliminary data suggest that the FOD scale is a reliable and valid instrument for assessing the multidimensional nature of the concern about developing dementia. Attention to what specifically is feared may help further our understanding of health behaviors, coping, and targeted supports.